Hermeneutics, Intertextuality and References to Politics. Observations on Translations of Rainer Maria Rilke, Bertolt Brecht and Günter Grass - Vital, Alberto (Estudios de Traducción, 2013)
The present article discusses passages of existing translations of Rilke, Brecht and Grass, considering the respective historical and discursive contexts of the works. The extreme richness of Rilkean language requires attention to phonemes and grammatical forms while literary hermeneutics facilitates comprehension. In his Buckow Elegies, Brecht establishes a relation of ironic intertextuality with Rilke but he subverts the genre by incorporating references to the political context of his time. The poem Die Lösung, motivated by the occurrences of the 17th of Juny 1953, displays the author’s auto irony. Also Grass intervenes frequently on political matters. Politische Landschaft is one of his poems that being initially very legible, turns arduous when received outside of its former political context.